STUDENTSâ PERCEPTIONS ABOUT PARAPHRASING AND THEIR COGNITIVE PROCESSES IN PARAPHRASING - Beleven Khrismawan; Utami Widiati (TEFLIN, 2013)
This qualitative study investigates studentsâ perceptions about paraphrasing and their cognitive and meta-cognitive processes in paraphrasing. Four Indonesian advanced EFL students enrolled in Applied Linguistics course of a graduate program in English Language Teaching of a state university in Malang were voluntarily willing to participate in thestudy. These four subjects did a paraphrasing task requiring them to do concurrent verbal reports whileparaphrasing three sentences and one paragraph.Following this, the subjects responded to a questionnaire and then participated in a retrospective interview. The data from the questionnaires were described qualitatively, whereas the verbal reports were transcribed andanalyzed for identification of cognitive and meta-cognitive strategies based on the framework of learning strategies by Chamot and Kupper (1989). The subjectsâ perceptions about paraphrasing appeared to be in line with the widely accepted definition and criteria of proper paraphrases. Additionally, the results of verbal reports show that the subjects used 21 cognitive and seven meta-cognitive strategies, reflecting the fact that most of the cognitive strategies used in the sentence level were applied in the paragraph level with some additions of strategies specific to paragraph development and synthesis such as finding the main idea and summarizing. Â